The Meaning of Simplicity in the GMIM Efrata Kanonang Congregation: Makna Kesederhanaan dalam Jemaat Gmim Efrata Kanonang - Meruntu, Michaila Yesaya Meruntu; Wungkana, Christophel Enistein Putra; Sumendap, Shania Kirana; Pioh, Meijesti Franata; Tarumingi, Denny Adry; Ratag, Linda Patricia; Tombeng, Ineke Marlien; Sendow, Mieke Nova (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper focuses on the praxis of simplicity among Minahasan affiliates of the Christian Evangelical Church in Minahasa (GMIM) as a spirituality that opposes consumeristic religion. A qualitative case study design was employed to gather data in the form of in-depth interviews, participant observation, and analysis of documents using purposely chosen congregants who always engage in simple living in family, ministry, and everyday life. Data were interpreted using thematic analysis, which was informed by the theological-hermeneutical framework. The results indicate that simplicity is not considered an absence but a planned, religious lifestyle of sufficiency, gratitude, humility, and reliance on God’s providence. In practical terms, the concept of simplicity is reflected in judicious handling of finances, low-profile consumption, non-competitive involvement in worship, and judicious use of social media. Congregants define this way of life as a protest against consumerist ideas such as extravagance, flaunting, and spiritual arrogance, which are becoming more pronounced in church activities and general society. This opposition is anchored in the merging of Minahasan cultural norms, particularly mapalus (mutual help) and the GMIM ethos of love, service, and modesty. This study concludes that the praxis of simplicity among GMIM congregants is a situational spirituality of resistance that protects and revitalizes the church’s theological identity. It provides pastoral implications for faith formation, leadership, and ecclesial practices that are useful in enabling congregants to resist religious consumerism while being involved in modern social life in the plural context of Indonesia.